2014
DOI: 10.1051/0004-6361/201423997
|View full text |Cite
|
Sign up to set email alerts
|

First detection of [N II] 205μm absorption in interstellar gas

Abstract: We present high resolution [N ii] 205 μm ( 3 P 1 − 3 P 0 ) spectra obtained with Herschel-HIFI towards a small sample of far-infrared bright star forming regions in the Galactic plane: W 31C (G10.6−0.4), W 49N (G43.2−0.1), W 51 (G49.5−0.4), and G34.3+0.1. The detection of the 205 μm line in absorption emphasises the importance of a high spectral resolution, and also offers a new tool for investigation of the WIM.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
1
15
1
Order By: Relevance
“…The electron density of the WIM is quite uncertain, and is often taken to be ∼ 0.01-0.1 cm −3 (e.g. Taylor & Cordes 1993;Goldsmith et al 2015;Persson et al 2014). Heiles et al (1996) found a low volume filling factor and a relatively high n e of 5 cm −3 , using 1.4-GHz radio recombination lines in the Galactic plane.…”
Section: [N Ii] Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron density of the WIM is quite uncertain, and is often taken to be ∼ 0.01-0.1 cm −3 (e.g. Taylor & Cordes 1993;Goldsmith et al 2015;Persson et al 2014). Heiles et al (1996) found a low volume filling factor and a relatively high n e of 5 cm −3 , using 1.4-GHz radio recombination lines in the Galactic plane.…”
Section: [N Ii] Linesmentioning
confidence: 99%
“…Therefore, the WIM component of them can be easily absorbed against background sources with high brightness temperatures. Using high-spectral-resolution observations from the HIFI instrument onboard Herschel, Persson et al (2014) detected absorption features of the [N II] 205-µm lines toward a few massive Galactic star-forming regions. They found that [N II] emission from ionised gas in the dense and hot H II regions is likely absorbed by widespread low-density and relatively lowtemperature WIM gas in the foreground.…”
Section: Absorptions To the Fine-structure Linesmentioning
confidence: 99%
“…5.5 below. The fractional contribution of WIM toward W31C is no more than 5%, based on the detection of N II absorption by Persson et al (2014), which leads to N(N + )/N(C + ) = 1/40, i.e., about twenty times lower than the [N]/[C] elemental abundance ratio in the gas.…”
Section: Locally Space-averaged Atomic Molecular and Total Densitiesmentioning
confidence: 99%
“…However, COBE had a 7 • beam and velocity resolution ∼1000 km s −1 and so could not provide details of the distribution of C + and N + in the Milky Way, locate the emission along the line of sight (LOS), or explore the dynamics of the gas traced by [C ii] and [N ii]. The Heterodyne Instrument in the Far-Infrared (HIFI, de Graauw et al 2010) on the Herschel Space Observatory (Pilbratt et al 2010) provided the first opportunity to obtain a large sample of velocity resolved [C ii] and [N ii] in the Galaxy in emission (Langer et al 2010;Goldsmith et al 2015) and absorption (Persson et al 2014;Gerin et al 2015). The determination of the properties of the ionized gas in emission and absorption probe higher and lower density phases of the ISM, respectively.…”
Section: Introductionmentioning
confidence: 99%